The Role of Women's Empowerment and Domestic Violence in Child Growth and Undernutrition in a Tribal and Rural Community in South India - Kavita Sethuraman (Research Paper No. 2008/15, 2008)
Moderate undernutrition continues to affect 46 per cent of children under 5 years of age and47 per cent of rural women in India. Women's lack of empowerment is believed to be an important factor in the persistent prevalence of undernutrition. In India, women'sempowerment often varies by community, with tribes sometimes being the most progressive. This paper explores the relationship between women's empowerment, domestic violence, maternal nutritional status, and the nutritional status and growth over six months in children aged 6 to 24 months in a rural and tribal community. This longitudinal observational study undertaken in rural Karnataka, India included tribal and rural subjects. Structured interviews with mothers were conducted and anthropometric measurements were obtained for 820 mother-child pairs, the follow-up rate after 6 months was 82 per cent. The data were analyzed by multivariate regression. Some degree of undernutrition was seen in 83.5 per cent of children and 72.4 per cent of mothers in the sample, moreover the prevalence of undernutrition increased among children at follow up. Domestic violence was experienced by 34 per cent of mothers in the sample. In multivariate analysis, biological variables explained most of the variance in nutritional status and child growth, followed by health-care seeking and women's empowerment variables; socio-economic variables explained the least variance. Women's empowerment variables were significantly associated with child nutrition on enrolment and child growth at follow-up. At follow-up, mother's prior lifetime experience of physical violence significantly undermined child growth in terms of weight-for-age, and older age at marriage and high mobility of mothers predicted less stunting in their children. In addition to the known investments needed to reduce undernutrition, improving women's nutrition, promoting gender equality, empowering women, and ending violence against women could further reduce the prevalence of undernutrition in this segment of the Indian population.